The Usage of Teaching Modules in Implementation of Independent Curriculum at Madrasas - Kamis, Riyadi Kamis (Kuttab: Jurnal Ilmiah Mahasiswa, 2023)
The Independent Curriculum (IKM) is a curriculum that provides creativity space and flexibility for madrasas in managing learning according to the needs, potential and characteristics of madrasas. One of the learning resources that can be used in IKM is teaching modules, which are independent teaching materials that contain materials, learning activities, and evaluations. This study aims to describe the management of learning through IKM teaching modules in madrasas. This research uses a qualitative approach with a case study method. The research subjects were teachers and students at one of the IKM pilot madrasahs in Malang City. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study show that the management of learning through the IKM teaching module in madrasah includes planning, implementation, and assessment. Planning is done by compiling a syllabus, learning implementation plan (RPP) IN 2013 CURRICULUM and teaching modules that are in accordance with learning outcomes (CP) and madrasah operational curriculum (KOM) in the independent curriculum. Implementation is carried out using teaching modules as the main teaching materials accompanied by other learning resources, such as textbooks, media, internet, etc. Implementation is also carried out by applying the principles of active, creative, effective and fun learning (PAKEM), as well as utilizing information technology in the presentation and distribution of teaching modules. The assessment is carried out using an integrated assessment instrument in the teaching module, as well as using a portfolio as evidence of CP achievement. This research has implications that the management of learning through IKM teaching modules in madrasas can improve the quality of learning and student learning outcomes.